2013
DOI: 10.1111/trf.12466
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic peripheral blood stem cell transplantation using reduced‐intensity conditioning in an outpatient setting in ABO‐incompatible patients: are survival and graft‐versus‐host disease different?

Abstract: Using this type of peripheral blood stem cell transplantation, minor ABO-mismatched allo-HSCT was associated with a higher incidence of aGVHD and cGVHD and with increased survival, albeit with no significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 38 publications
0
14
0
2
Order By: Relevance
“…Ludajic et al [27] observed that a minor ABO-mismatch represents a significant risk factor for acute GVHD (grade II–IV) with an estimated risk increase of almost 3-fold, and even 4-fold for severe acute GVHD (grade III–IV). Gutiérrez-Aguirre et al [28] analyzed a cohort of patients exclusively receiving RIC and found the highest rate of acute GVHD in minor ABO-mismatched transplant recipients (25%) compared with ABO-identical (20.5%) and major ABO-mismatched cases (15.4%). Other publications observe no influence of ABO mismatch on the incidence of clinically significant acute GVHD [6, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Ludajic et al [27] observed that a minor ABO-mismatch represents a significant risk factor for acute GVHD (grade II–IV) with an estimated risk increase of almost 3-fold, and even 4-fold for severe acute GVHD (grade III–IV). Gutiérrez-Aguirre et al [28] analyzed a cohort of patients exclusively receiving RIC and found the highest rate of acute GVHD in minor ABO-mismatched transplant recipients (25%) compared with ABO-identical (20.5%) and major ABO-mismatched cases (15.4%). Other publications observe no influence of ABO mismatch on the incidence of clinically significant acute GVHD [6, 29].…”
Section: Discussionmentioning
confidence: 99%
“…MSCs from the bone marrow (BM-MSCs) were originally described by Friedenstein et al as non-phagocytic and non-hematopoietic cells and adherent to plastic [4]. Over the last 15 years, there has been an explosion in the reports of MSCs isolated from a variety of other adult sources, including skin [5], adipose tissue [6], umbilical cord blood [7,8] and matrix, peripheral blood [9], tendons [10,11], amnion [12][13][14], and bone [15][16][17]. Their plasticity, immunosuppressive potential, immuno-modulatory properties [18,19], and trophic activity [20,21] make MSCs critical players in tissue homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…All but one of the studies reporting on the incidence of GVHD showed no influence of ABO-mismatched transplantation on development or severity of chronic GVHD. Gutiérrez-Aguirre et al [46] observed a higher incidence of chronic GVHD in the context of minor ABO mismatch (35%), in contrast to ABO-identical (30.8%) and major ABO-mismatched transplants.…”
Section: Graft-versus-host Diseasementioning
confidence: 99%
“…However, results of cohort and registry studies are conflicting. Two registry studies found a higher risk for NRM in the RIC cohort, one of those also for major ABO-mismatched cases if myeloablative conditioning was applied [6,36], whereas some cohort studies observed an increased risk for patients after minor, major or bi-directional ABO-mismatched transplants [4,8,46] (table 2).…”
Section: Non-relapse Mortalitymentioning
confidence: 99%
See 1 more Smart Citation